The Relationships Between Athletes' Perceptions of Coach-Created Motivational Climate, Self-Talk, and Self-Efficacy in Youth Soccer. Issue 1 (2nd January 2016) - Zourbanos, Nikos; Haznadar, Adisa; Papaioannou, Athanasios; Tzioumakis, Yannis; Krommidas, Charalambos; Hatzigeorgiadis, Antonis
Abstract : The purpose of this study was to explore the mediating role of self-talk in the relationship between athletes' perceptions of coach-created motivational climate and athletes' self-efficacy. Two hundred eighty-nine youth soccer players ( M = 11.63 years, SD = 1.55 years) completed the Automatic Self-Talk Questionnaire for Sport, the Empowering and Disempowering Motivational Climate Questionnaire, and a self-efficacy measure for soccer. The results showed that only positive and not negative self-talk mediated the relationship between empowering motivational climate and self-efficacy, whereas no relationship emerged between disempowering climate and self-efficacy, highlighting the role of self-talk explaining this relationship.